Aortic dissection after coronary artery bypass grafting - Brykczyński, Mirosław; Ślozowski, Paweł; Mokrzycki, Krzysztof; Żukowski, Maciej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Aortic dissection is a complication after CABG surgery which is difficult to treat. There are no guidelines or algorithms, mostly because this condition is rare. We are describing three cases of successful treatment of acute aortic dissection, which occurred at different times after the previous cardiac surgery. We are presenting our surgical approach and postoperative care. Treatment of this condition is connected with a high risk and necessity of prolonged intensive care because of perioperative complications.